# trigonometry

Prove:
tan2x+sec2x = cosx+sinx/ cosx-sinx

1. 👍
2. 👎
3. 👁
1. I am sure you meant :
tan2x+sec2x = (cosx+sinx)/(cosx-sinx)

LS
= sin2x/cos2x + 1/cos2x
= (sin2x +1)/cos2x
= (2sinxcosx + sin^2x + cos^2x)/(cos^2x - sin^2x)
= (sinx + cosx)^2/[(cosx-sinx)(cosx+sinx)]
= (sinx + cosx)/(cosx - sinx)
= RS

Q.E.D.

1. 👍
2. 👎
2. This time start from the right-hand side by taking advantage of the term cos(x)-sin(x):
(cos(x)+sin(x))/(cos(x)-sin(x))
multiply top and bottom by cos(x)+sin(x)
(cos(x)+sin(x))^sup2;/(cos²(x)-sin²(x)
=(cos²(x)+sin²(x)+2sin(x)cos(x))/(cos²(x)-sin²(x))
=(1+sin(2x))/cos(2x)
=sec(2x)+tan(2x)

1. 👍
2. 👎
3. Thank you so much Reiny and Mathmate. Both of you guys gave me great ways to solving this problem.

1. 👍
2. 👎

## Similar Questions

1. ### trigonometry

how do i simplify (secx - cosx) / sinx? i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i changed sec x to 1/ cosx so that i had ((1/cosx)/ sinx) - (cos x / sinx) after that i get stuck

3. ### math;)

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the

4. ### Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30º, the two sides are not equal, they differ by 1 oh , thank you Mr

1. ### Math

(sinx - cosx)(sinx + cosx) = 2sin^2x -1 I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx) into 1 and would it still have the same identity?

Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities? Check all that

3. ### Calculus

determine the absolute extreme values of the function f(x)=sinx-cosx+6 on the interval 0

1. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

2. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

3. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

4. ### trig

How do I prove these trig identities? secx-cosx/tanx =sinx And 1+sinx/cosx+ cox/ 1+sinx=2secx